2015
DOI: 10.1111/are.12703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of density, PVC-tubes and feeding time on growth, stress and aggression in African catfish (Clarias gariepinus)

Abstract: Successive exposure to aquaculture‐related stressors may compromise the allostatic capacity of African catfish and lead to allostatic overload and poor welfare. Therefore, we tested the effect of (i) feeding during the light or dark phase, (ii) density (51 fish per 140 L versus 51 fish per 43 L) and (iii) altered available resting space/shelter on stress handling were studied in African catfish (Clarias gariepinus). Available resting space/shelter was manipulated by providing PVC‐tubes in the tanks. Growth, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 68 publications
6
18
1
3
Order By: Relevance
“…As described above, their unique body shape could be another strong reason that evolved them to be adapted for better growth performance under dark condition. Thus, the overall finding of the present study having better growth parameters in dark condition corroborates the results obtained by some other studies (Appelbaum & Kamler, ; Boerrigter, Bos, Vis, Spanings, & Flik, ; Britz & Pienaar, ; Rahmah et al, ). In a study with C. gariepinus , Boerrigter et al () showed that night feeding enhanced growth and reduced feed conversion ratio in this species compared to day‐feeding strategy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As described above, their unique body shape could be another strong reason that evolved them to be adapted for better growth performance under dark condition. Thus, the overall finding of the present study having better growth parameters in dark condition corroborates the results obtained by some other studies (Appelbaum & Kamler, ; Boerrigter, Bos, Vis, Spanings, & Flik, ; Britz & Pienaar, ; Rahmah et al, ). In a study with C. gariepinus , Boerrigter et al () showed that night feeding enhanced growth and reduced feed conversion ratio in this species compared to day‐feeding strategy.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the overall finding of the present study having better growth parameters in dark condition corroborates the results obtained by some other studies (Appelbaum & Kamler, ; Boerrigter, Bos, Vis, Spanings, & Flik, ; Britz & Pienaar, ; Rahmah et al, ). In a study with C. gariepinus , Boerrigter et al () showed that night feeding enhanced growth and reduced feed conversion ratio in this species compared to day‐feeding strategy. Catfish prefer swimming and feeding activities under darkness which have also been supported by Rahmah et al () in their study with bagrid catfish ( M. nemurus ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It should also be noted that, previously it has been reported that the highest levels of cortisol following stress were at 1 h post stressor exposure (van de Nieuwegiessen et al, 2008), but here, however, the highest levels were directly following the stressor. Similar observations were made after applying the same stressor (15 min forced air exposure and crowding) in another series of experiments (Boerrigter et al, 2015b) on C. gariepinus. The comparatively rapid occurrence of the peak as well as the swift recovery may have masked day and night differences in the present experiments.…”
Section: P L a S M A C O Rt I S O Lsupporting
confidence: 77%
“…The existence of daily feeding rhythms with an active diurnal or nocturnal behaviour has been documented in a number of fish species (Boerrigter, van den Bos, van de Vis, Spanings & Flik, 2016;Figueiredo-Silva, Corraze, Sanchez-Gurmaches, Guti errez & Valente, 2010;Kitagawa et al, 2015;L opez-Olmeda, L opez-Garc ıa et al, 2012;Mattos, Filho, Santos et al,2016;Oliveira et al, 2013). A number of studies have demonstrated that feeding time affects growth performance, food conversion efficiency (Boerrigter et al, 2016;Bolliet, Jarry & Boujard, 2004;Caldini, Pereira, Rebouc ßas & do Carmo e S a, 2013; Guill en, Moyano & Y ufera, 2015;Kitagawa et al, 2015;Mattos, Filho, Santos et al, 2016) and even body composition (Guevara et al, 2015;Nocskc-Hallin, Spieler, Parker & Suttle, 1985). Since in the natural environment, food is hardly constantly available, and is usually restricted to a particular time when its availability is highest.…”
mentioning
confidence: 99%